البيوع والشراء المعاصرة عند المذاهب الفقهية الأربعة - Huda, Muhammad Miftahul; Rais, Pandi (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2018)
Abstract:Buying and selling is one of the most important areas of business, and Islamic law has confirmed that is permissible under certain conditions. Therefore, the researcher explained the nature of the contract and its legitimacy and types, so that the research is clear in theory when dealing with the practical application of Islamic banking. This research is based on a deductive reasoning method. It began by compiling the original references from the general and particular books of Islamic jurisprudence and the efforts of the four schools approved. As a result of this research, the current sales are the legitimate ones, they are different from the general sale picture, including: 1) bargaining sales, 2) sales of the trust, and 3) the exchange contract. And the contemporary sale that are forbidden by sharia, it’s the sale that is forbidden by the Sharia for a defect in its pillars or a lack of its conditions. The most important things are: 1) sales are forbidden by Sharia because of gharar and ignorance, 2) sales are forbidden because of the sanctity of the eye of sale, 3) sales are forbidden because it distracts from acts of worship. Keywords: Buying and selling, contemporary, jurisprudence doctrines